2022
DOI: 10.1038/s41598-022-10981-8
|View full text |Cite
|
Sign up to set email alerts
|

Sensorimotor inhibition during emotional processing

Abstract: Visual processing of emotional stimuli has been shown to engage complex cortical and subcortical networks, but it is still unclear how it affects sensorimotor integration processes. To fill this gap, here, we used a TMS protocol named short-latency afferent inhibition (SAI), capturing sensorimotor interactions, while healthy participants were observing emotional body language (EBL) and International Affective Picture System (IAPS) stimuli. Participants were presented with emotional (fear- and happiness-related… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 84 publications
0
11
0
Order By: Relevance
“…Transcranial magnetic stimulation (TMS) studies have shown that static pictures of fearful EBL exert an inhibitory, rapid effect on corticospinal excitability as well as on intracortical facilitatory mechanisms within the primary motor cortex (M1) of the observer (Borgomaneri et al, 2015b, 2015c, 2017) when compared with positive EBL and nonemotional body movements. Furthermore, in a previous TMS work by our group, we found that fearful EBL stimuli, differently from positive and nonemotional stimuli, enhance short‐latency somatosensory afferent inhibition (SAI) at 120 ms after the stimulus onset, hence demonstrating that the observation of fearful EBL produces an early reduction of M1 excitability mediated by sensorimotor integration mechanisms involving the primary somatosensory cortex (S1) (Botta et al, 2022). Moreover, in behavioral tasks, EBL static pictures induced shorter response times, when compared with positive EBL and nonemotional body language (Borgomaneri et al, 2020; Botta et al, 2021).…”
Section: Introductionmentioning
confidence: 71%
See 3 more Smart Citations
“…Transcranial magnetic stimulation (TMS) studies have shown that static pictures of fearful EBL exert an inhibitory, rapid effect on corticospinal excitability as well as on intracortical facilitatory mechanisms within the primary motor cortex (M1) of the observer (Borgomaneri et al, 2015b, 2015c, 2017) when compared with positive EBL and nonemotional body movements. Furthermore, in a previous TMS work by our group, we found that fearful EBL stimuli, differently from positive and nonemotional stimuli, enhance short‐latency somatosensory afferent inhibition (SAI) at 120 ms after the stimulus onset, hence demonstrating that the observation of fearful EBL produces an early reduction of M1 excitability mediated by sensorimotor integration mechanisms involving the primary somatosensory cortex (S1) (Botta et al, 2022). Moreover, in behavioral tasks, EBL static pictures induced shorter response times, when compared with positive EBL and nonemotional body language (Borgomaneri et al, 2020; Botta et al, 2021).…”
Section: Introductionmentioning
confidence: 71%
“…This study aimed to test whether observation of EBL was able to modulate cortical activity in sensorimotor areas, specifically ERPs and cortical oscillations in the mu‐alpha and lower beta frequency bands, at short latencies (around 100 ms after the onset of the EBL stimulus). We built on our previous TMS findings that sensorimotor integration, as tested in M1 using the SAI protocol, is modulated during the processing of static images depicting fear EBL, already at 120 ms from the stimulus onset (Botta et al, 2022). Based on current knowledge of the neurophysiological cortico‐cortical mechanism underlying the SAI effect (Turco et al, 2018), and the increasing recognition of a key role of primary sensorimotor areas in the perception of others' actions and emotions (Adolphs et al, 2000; Bufalari et al, 2007; Gazzola et al, 2012; Keysers et al, 2010; Paracampo et al, 2017; Pitcher et al, 2008), we hypothesized that modulation of sensorimotor integration during observation of fear EBL was driven by increased activity in S1 – reflecting increased sensory vigilance – and an inhibitory effect on M1 excitability – reflecting a freezing response to potentially threatening signals.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…-License CC BYHashemi et al, 2019) and the basal ganglia (BG), and cortical, such as the primary(Borgomaneri et al, 2015(Borgomaneri et al, , 2021Botta et al, 2022;Ferrari et al, 2021;Hortensius et al, 2016;Schutter et al, 2008) and secondary motor cortices (i.e., the supplementary motor (SMA) and premotor (PM) cortex;Diano et al, 2017;Grèzes et al, 2014; Grèzes & Dezecache, 2014;Rizzo et al, 2018;Rolls et al, 2022), as well as to the cerebellum(Pierce & Péron, 2020), influencing action readiness.Other than via the AMY and other subcortical centers, the PUL can also constrain action maps through its diffuse connections with the dorsal visual stream, known to be involved in the perception of emotional expressions(Engelen et al, 2015(Engelen et al, , 2018, and the translation into action opportunities, in connection with the premotor cortex(Cisek, 2007;Orban, Lanzilotto, et al, 2021;Orban, Sepe, et al, 2021;Rizzolatti et al, 2014). For instance, and in line with monkey studies, it has recently been shown that intraparietal and premotor regions, as well as the AMY, respond to approaching threatening individuals that are about to invade our peripersonal space, in order to rapidly prepare defensive actions (de Borst & de Gelder, 2022).6 -License CC BY…”
mentioning
confidence: 99%